The Fourth Law of Behavior Genetics. (August 2015) - Chabris, Christopher F.; Lee, James J.; Cesarini, David; Benjamin, Daniel J.; Laibson, David I.
Behavior genetics is the study of the relationship between genetic variation and psychological traits.Turkheimer (2000) proposed "Three Laws of Behavior Genetics" based on empirical regularities observed in studies of twins and other kinships. On the basis of molecular studies that have measured DNA variation directly, we propose a Fourth Law of Behavior Genetics: "A typical human behavioral trait is associated with very many genetic variants, each of which accounts for a very small percentage of the behavioral variability." This law explains several consistent patterns in the results of gene-discovery studies, including the failure of candidate-gene studies to robustly replicate, the need for genome-wide association studies (and why such studies have a much stronger replication record), and the crucial importance of extremely large samples in these endeavors. We review the evidence in favor of the Fourth Law and discuss its implications for the design and interpretation of gene-behavior research.